2021
DOI: 10.1515/nanoph-2021-0122
|View full text |Cite
|
Sign up to set email alerts
|

Monolithic integrated emitting-detecting configuration based on strained Ge microbridge

Abstract: The strain technology is accelerating the progress on the CMOS compatible Ge-on-Si laser source. Here, we report a monolithically integrated microbridge-based emitting-detecting configuration, equipped with lateral p–i–n junctions, waveguide and gratings. The operating wavelength range of the emitting bridge and the detecting bridge are matched through the designed same dimensions of the two microbridges, as well as the strain. Strain-enhanced spontaneous emission and the effect of spectra red-shifting on low-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…These grooves had a width of 308 nm and a spacing of 132 nm. 10) PECVD was used to fill the grooves created in step (8) with SiO 2 , forming a distributed Bragg reflector. 11) Metal electrodes were deposited on the P and N regions through sputtering etching and deposition to establish the strip metal electrodes.…”
Section: Discussionmentioning
confidence: 99%
“…These grooves had a width of 308 nm and a spacing of 132 nm. 10) PECVD was used to fill the grooves created in step (8) with SiO 2 , forming a distributed Bragg reflector. 11) Metal electrodes were deposited on the P and N regions through sputtering etching and deposition to establish the strip metal electrodes.…”
Section: Discussionmentioning
confidence: 99%
“…They have demonstrated that using alloying method and special structures, compact group IV lasers can be realized with a low threshold value (an optical pumping threshold density of ∼3.0 kW•cm −2 ) and high efficiency (a differential quantum efficiency close to 100%) [36]. There are also some research efforts on Ge LEDs and photodetectors [38,39].…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that the uniaxial tensile strain can be largely enhanced in the MB, offering further improved luminescence efficiency [8][9][10][11][12][13]. There are several reports on light emitting diode devices based on Ge MB structures [14,15]. In these reports standards Si (100) substrates have used and bridge directions were set to be <001> direction.…”
Section: Introductionmentioning
confidence: 99%